Sewage sludge ashes as a primary catalyst for the abatement of tar in biomass gasification: Bubbling versus spouted‐fluidized bed configuration. (27th April 2021) - Ruoppolo, Giovanna; Miccio, Francesco; Miccio, Michele; Brachi, Paola; Chirone, Riccardo
Abstract: Sewage sludge (SS) ashes, rich in iron and calcium, have been tested as a primary catalyst during air gasification of commercial wood pellets in a pre‐pilot scale fluidized bed (FB) reactor. The shifting from a conventional fluidized bed to a spouted‐fluidized bed configuration has been assessed on the catalyst performance. Specifically, at constant total air inlet flow rate, two different values of the air flow rate in a central spouting nozzle have been adopted, which correspond to 20% and 37.5% of the total inlet gas flow rate. Under the conventional fluidized bed configuration (i.e., bubbling regime), SS ashes exhibit good performance in term of tar reduction (about 20% decrease compared to a bed of inert silica sand), without significantly affecting the syngas composition. Concerning the transition to the spouted‐fluid bed configuration, the gas‐solid contact efficiency is enhanced at lower air flow rates through the central nozzle, with respect to the FB regime, leading to better gasification performance in terms of tar reduction (around 40% less) and syngas quality. A slightly worse gasification performance is obtained at high values of air flow rate in the central nozzle, due to a progressive increase of gas bed bypassing. Furthermore, moving from the conventional FB configuration to the spouted‐fluid bed one dramatically boosts the elutriation rate of carbon fines as well as the attrition of catalyst particles.